2005
DOI: 10.4103/0019-5545.46080
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-induced acute colonic (pseudo) obstruction (Ogilvie syndrome)

Abstract: Patients on antidepressant drugs commonly complain of dryness of the mouth, tremors, blurring of vision and constipation, which are attributed to the anticholinergic action of the drugs. We report two cases of gastrointestinal complications (pseudo-intestinal obstruction), which are considered rare according to a review of the literature. This condition is also known as Ogilvie syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…This case reported agrees with the fact that intestinal pseudo-obstruction denotes a syndrome characterized by a clinical picture suggestive of mechanical obstruction in the absence of any demonstrable evidence of such obstruction in the intestine but mimics it in presentation [1,11,12]. The aetiology of this reported case of Intestinal Obstruction is in keeping with the myriad of associated causes which have been documented and reviewed which includes drugs like Tricyclics [1,3,7,12]. After a mechanical cause of obstruction has been excluded by barium enema, the treatment is conservative, with intravenous fluids, nasogastric suction and colonic decompression [12].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This case reported agrees with the fact that intestinal pseudo-obstruction denotes a syndrome characterized by a clinical picture suggestive of mechanical obstruction in the absence of any demonstrable evidence of such obstruction in the intestine but mimics it in presentation [1,11,12]. The aetiology of this reported case of Intestinal Obstruction is in keeping with the myriad of associated causes which have been documented and reviewed which includes drugs like Tricyclics [1,3,7,12]. After a mechanical cause of obstruction has been excluded by barium enema, the treatment is conservative, with intravenous fluids, nasogastric suction and colonic decompression [12].…”
Section: Discussionsupporting
confidence: 90%
“…Previous case reported cases of intestinal pseudo obstruction in 60 and 65 year olds and another study on the Pattern of Intestinal Obstruction in Nigeria, reported a mean age of occurrence of 39 years and a preponderance of male gender in treated cases [1,6]. Adhesive obstruction was found to be the most cause in the report with a prevalence of 44% [6].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…As is evident from Tables 1 to 6 , tricyclic antidepressants are poorly tolerated compared to the newer antidepressants. Additionally, there are multiple case reports implicating various antidepressants for induction of hypomania/mania,[ 87 – 96 ] hyponatremia/Syndrome of inappropriate antidiuretic hormone secretion (SIADH),[ 97 99 ] extrapyramidal symptoms,[ 100 ] acute colonic (pseudo) obstruction (Ogilvie syndrome),[ 101 102 ] psychosis,[ 103 ] hypertension,[ 104 ] vascular headache,[ 105 ] torsades de pointes,[ 106 ] alopecia,[ 107 ] cardiogenic shock,[ 108 ] seizures,[ 109 110 ] galactorrhoea,[ 111 ] mania on withdrawal of antidepressants,[ 112 ] upper gastrointestinal bleeding,[ 113 ] bleeding gums,[ 114 ] serotonin syndrome[ 116 117 ] etc [ Table 9 ].…”
Section: Introductionmentioning
confidence: 99%